2019
DOI: 10.1158/2326-6066.cir-18-0481
|View full text |Cite
|
Sign up to set email alerts
|

Lactate-Mediated Acidification of Tumor Microenvironment Induces Apoptosis of Liver-Resident NK Cells in Colorectal Liver Metastasis

Abstract: Colorectal cancer is the third most common malignancy worldwide, with 1.3 million new cases annually. Metastasis to the liver is a leading cause of mortality in these patients. In human liver, metastatic cancer cells must evade populations of liver-resident natural killer (NK) cells with potent cytotoxic capabilities. Here, we investigated how these tumors evade liver NK-cell surveillance. Tissue biopsies were obtained from patients undergoing resection of colorectal liver metastasis (CRLM, n ¼ 18), from the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 52 publications
3
183
0
2
Order By: Relevance
“…Lactate accumulation has been associated with reduced NK cell cytotoxicity and downregulation of NKp46 (141,142). The acidification of the TME has been shown to induce apoptosis of liver-resident NK cells in colorectal cancer liver metastases (143). The neutralization of the TME restored the cytotoxic activity of NK cells enhancing NKG2D expression (144).…”
Section: Immunosuppressive Properties Of the Tme On Nk Cellsmentioning
confidence: 99%
“…Lactate accumulation has been associated with reduced NK cell cytotoxicity and downregulation of NKp46 (141,142). The acidification of the TME has been shown to induce apoptosis of liver-resident NK cells in colorectal cancer liver metastases (143). The neutralization of the TME restored the cytotoxic activity of NK cells enhancing NKG2D expression (144).…”
Section: Immunosuppressive Properties Of the Tme On Nk Cellsmentioning
confidence: 99%
“…17 It is widely established that tumor-derived lactic acid and acidification impair T and NK cell function. 14,84,112,116,117 NK cells from Ldha-depleted tumors show improved cytolytic function and lactate treatment of NK cells inhibits cytolytic function in vitro. Furthermore, LDH-A expression in melanoma biopsies correlated with T cell activity and…”
Section: Immunolog Ic Al Cons Equen Ce S Of the Warburg Effec T-a Mmentioning
confidence: 99%
“…Intracellular acidification associated with the uptake of lactic acid by NK cells was shown to interfere with the regulation of NFAT and, in turn, expression of IFN-γ. Elsewhere, Harmon et al [150] reported that acidification due to lactate production induced apoptosis of liver-resident NK cells in colorectal liver metastasis tumors. In the study, lactate accumulation brought about a reduction of the pH in the TME.…”
Section: Lactatementioning
confidence: 99%
“…Cytokines have been shown to strongly affect NK cell metabolism [155]. Among them, IL-15 is the most widely studied [156] PD-1 Impairs lytic granule polarization; likely contributes to impaired NK anti-tumor immunity; in T cells PD-1 blocks glycolysis and glutaminolysis [47,49,54] Tumor microenvironment Adenosine Impairs cytotoxicity, glycolysis and alters mitochondrial respiration [86] TGF-β Inhibits mTOR in NK cells; impairs oxidative phosphorylation, glycolytic capacity and capacity and expression of CD71 [13,131] Hypoxia Impairs function and metabolism of NK cells; effects of NK cells are condition specific and somewhat inconclusive [137,140] Lactate Impairs NK cell activation, function and IFN-γ production [149][150][151] Despite the growing body of work that continues to uncover new mechanisms which tumors use to evade NK cell-mediated recognition and killing our understanding of NK cell metabolism in pathological settings lacks significant knowledge. For example, many of the studies on NK cell metabolism are carried out in ex vivo environments not representative of TME conditions, precluding accurate mechanistic insights to be elucidated.…”
Section: Strategies To Target Immunometabolic Reprogramming Of Nk Celmentioning
confidence: 99%